Association Among Television and Computer/Video Game Use, Victimization, and Suicide Risk Among U.S. High School Students. Issue 5 (March 2021) - Rostad, Whitney L.; Basile, Kathleen C.; Clayton, Heather B.
With the increasing popularity of mobile Internet devices, the exposure of adolescents to media has significantly increased. There is limited information about associations between the types and frequency of media use and experiences of violence victimization and suicide risk. The current study sought to examine the association of bullying and teen dating violence (TDV) victimization, suicide risk with different types of media use (i.e., television and computer/video game use), and number of total media use hours per school day. Data from the nationally representative 2015 Youth Risk Behavior Survey ( n = 15, 624) were used to examine the association between media use and violence victimization and suicide risk. Logistic regression models generated prevalence ratios adjusted for demographic characteristics and substance use behaviors to identify significant associations between media use and victimization and suicide risk, stratified by gender. Media use was associated with TDV victimization for male students only, while media use was related to experiences of bullying and suicide risk for both male and female students. In addition, limited (2 or fewer hours) and excessive (5 or more hours) media use emerged as significant correlates of suicide risk and bullying victimization, with limited media use associated with decreased risk and excessive media use with increased risk. Comprehensive, cross-cutting efforts to prevent different forms of victimization should take into account media use and its potential association with adolescent victimization and suicide risk. The current study results suggest limiting adolescent media use, as part of comprehensive prevention programming, might relate to reductions in risk for victimization and suicide.